Serum concentrations of angiogenic cytokines in Waldenstrom macroglobulinaemia: The ratio of angiopoietin-1 to angiopoietin-2 and angiogenin correlate with disease severity - Anagnostopoulos, A.; Eleftherakis-Papaiakovou, V.; Zervas, K.; Kastritis, E.; Tsionos, K.; Bamias, A.; Meletis, J.; Dimopoulos, M.A.; Terpos, E. (British Journal of Haematology, 2007)
Angiogenesis represents an essential step of disease progression in several haematological malignancies. Microvessel density is increased in 30% of patients with Waldenstrom macroglobulinaemia (WM), but there is very limited information regarding the role of angiogenic cytokines in this disease. Serum levels of vascular endothelial growth factor (VEGF), VEGF-A, angiogenin, angiopoietin (Ang)-1 and -2, and basic fibroblast growth factor (bFGF) were evaluated in 56 WM patients at different disease phases (24 untreated, 20 relapsed/refractory and 12 patients at remission) and 11 patients with immunoglobulin M type monoclonal gammopathy of undetermined significance (IgM-MGUS). All patients had increased levels of angiogenin, VEGF, VEGF-A, and bFGF compared with controls. The Ang-1/Ang-2 ratio was reduced in WM but not in IgM-MGUS patients. Angiogenin levels correlated with disease status: when compared with healthy subjects, patients with IgM-MGUS and untreated WM patients had increased angiogenin serum levels, which were higher in untreated WM patients than in MGUS. WM patients at remission had lower angiogenin serum levels compared with untreated patients, but these levels were increased again in active disease post-therapy. Angiogenin also correlated with albumin levels, while VEGF-A correlated with β2-microglobulin (β2M). Ang-1/Ang-2 ratio showed a strong, negative correlation with β2M, and positive correlation with albumin, haemoglobin and lymphadenopathy. Our results indicate a potential use of angiogenin levels for follow-up in WM and angiogenic molecules as targets for the development of novel anti-WM agents. © 2007 The Authors.
Keywords: Angiogenesis; Angiogenin; Angiopoietins; Vascular endothelial growth factor; Waldenström macroglobulinaemia